Predictive validity of objective measures of physical fitness for the new onset of mental disorders in adolescents and young adults. Issue 6 (21st January 2019) - Tacchi, Mary Jane; Heggelund, Jorn; Scott, Jan
Abstract : Aim: To systematically review evidence that objectively assessed level of physical fitness is associated with future risk of adverse mental health outcomes during the peak age range for onset of adult mental disorders. Methods: Searches of Electronic databases (EBSCOhost, SPORTDISCUS, EMBASE, MedLINE, Cochrane database, CINAHL, PsychInfo, and Dissertation Abstracts), supplemented by hand searches of journals, conference proceedings and citations. Random‐effects meta‐analysis models were used to pool the intervention effects. Results: Eight studies of adolescents and young adults were included in the qualitative review and six studies derived from four independent cohorts were included in the statistical analyses. Most publications reported on large samples (including >1 million), but male conscripts were over‐represented in the study cohorts; quality of included studies was modest, and heterogeneity was significant. Meta‐analytic estimates were conducted for different adverse mental health outcomes, but all showed an inverse association between fitness and incidence of mental disorders or suicidality. Overall, higher level of physical fitness was associated with lower rates of onset of mental health problems (odds ratio: 0.59; 95% confidence intervals: 0.54, 0.65). Conclusions: All eligible studies were undertaken since 2010, suggesting this is an emerging but unfinished field of research. The study design and methodological limitations indicate that the reported results should be treated with caution. However, if the meta‐analytic findings are reliably replicated for new cohorts of males and females, they have implications for research into the prevention of non‐communicable diseases, as our review suggests that interventions should target physical and mental health in equal measure.